IMPLEMENTASI PERATURAN BUPATI MAJALENGKA NOMOR 54 TAHUN 2021 TENTANG PENCEGAHAN PERKAWINAN PADA USIA ANAK DI KECAMATAN SINDANGWANGI - Dede Al Mustaqim; Youdhisthira Wibowo Andra; Rahmat Fauzi; Miftahul Munir; Abdul Fatakh (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2026)
Child marriage remains a serious issue in Indonesia despite the enactment of Law Number 16 of 2019, which raised the minimum legal age for marriage to 19 years. As a derivative regulation, the Government of Majalengka Regency issued Regent Regulation Number 54 of 2021 concerning the Prevention of Child Marriage, the implementation of which at the sub-district level is a key factor in the policy’s success. The research method used is a qualitative approach with a phenomenological type of study, focusing on the subjective experiences of actors involved in implementing the policy. The results show that the implementation of the Regent Regulation in Sindangwangi Sub-district is carried out through an adaptive and contextual approach, where prevention materials are not delivered through standalone programs but are integrated into PKK activities, family planning programs, community health posts (posyandu), Legal Awareness Village initiatives, as well as advisories during marriage ceremonies. The division of roles among institutions functions clearly: the sub-district government acts as coordinator and supervisor; the Office of Religious Affairs (KUA) serves as the front line in age verification and religious education; Family Planning Field Officers (PLKB) provide technical assistance in reproductive health and Marriage Age Maturity (PUP); while village governments and religious leaders act as facilitators at the community level. Flagship programs include structured counseling by DP3AKB, PUP and ElSIMIL programs by PLKB, School-Age Youth Guidance (BRUS) by KUA, as well as contextual outreach through digital media and religious forums. Although two cases of child marriage were still recorded in 2022, cross-sectoral collaboration operating synergistically has created a comprehensive prevention ecosystem.